Covid-19 and Increased Risk of Physician Suicide: A Call to Detoxify the U.S. Medical System - Kakarala, Sophia E.; Prigerson, Holly G. (Frontiers in Psychiatry, 2022)
Suicide among physicians is a longstanding problem, with risk factors exacerbated by the coronavirus disease 2019 (COVID-19) pandemic. In this article, we explore suicidal thoughts and behaviors among physicians and risk factors created or intensified by the work environment, such as overwork and loss of autonomy. We discuss the ways in which the COVID-19 pandemic has made the medical work environment more stressful (e.g. greater exposure to traumatic experiences and employment insecurity) and, consequently, elevated physician suicide risk. We also review evidence that the medical system in the United States has not adequately protected physicians' mental health. Lack of confidentiality, stigma, cost, and time, as well as intrusive medical licensing applications, remain barriers to physicians seeking help. Work pressures imposed by insurance companies and financial incentives to increase revenue while cutting costs compound physicians' work stress. We conclude that system-wide changes to the practice of medicine and policies regarding healthcare delivery are needed to improve physicians' work environments, as is research addressing the impact of the interventions to reduce their suicidal risk. The proposed changes, and greater access to timely and confidential mental health services amid and in the aftermath of the pandemic, may prove promising approaches to reduce physicians' suicide risk.